"Who Can We Tell Survivors to Call?" The Institutionalization of Criminal-Legal Interventions in a Domestic Violence Organization. (1st July 2019) - Weiss, Benjamin R
Abstract: Although criminal-legal interventions became accepted as the best response to domestic violence early in the battered women's movement, recent literature suggests that such interventions are often ineffective in reducing rates of violence. Despite this evidence, domestic violence advocates still emphasize criminal-legal interventions over alternatives when working with victims of violence. The author spent thirteen months observing domestic violence advocates in a feminist nonprofit organization to learn how the paradoxical reliance on criminal-legal interventions is reproduced. The paper identifies three mechanisms. First, information on criminal-legal interventions is emphasized more than other interventions in advocate training. Second, nonprofit staff present extreme examples of abuse and their associated criminal-legal interventions while training advocates rather than describing the types of abuse more typically brought to the organization. Finally, staff establish protocols for handling advocates' discontent with criminal-legal interventions which makes further collaboration between volunteers and the police possible. Together, these mechanisms reproduce criminal-legal interventions by limiting advocates' knowledge of the variety of alternative interventions. Practically, this work suggests several ways for advocates to destabilize ineffective organizational practices. Theoretically, the author shows that normative institutions are reproduced not just through socialization and coercion, but also through a lack of alternatives.